Communicating with children and families about obesity and weight‐related topics: a scoping review of best practices. (26th November 2016) - McPherson, A. C.; Hamilton, J.; Kingsnorth, S.; Knibbe, T. J.; Peters, M.; Swift, J. A.; Krog, K.; Chen, L.; Steinberg, A.; Ball, G. D. C.
Summary: Background: Healthcare professionals have called for direction on how best to communicate about weight‐related topics with children and families. Established scoping review methodology was used to answer the question: 'How can healthcare professionals best communicate with children and their families about obesity and weight‐related topics?' Methods: We searched four scientific databases, two grey literature repositories and 14 key journals (2005–2016). Inclusion criteria were (i) children up to and including 18 years of age and/or their parents; (ii) communication about healthy weight, overweight, obesity or healthy/active living; and (iii) healthcare setting. Results: Thirty‐two articles were included. Evidence‐based best practices were largely absent from the literature, although the following guiding principles were identified: (i) include all stakeholders in discussions; (ii) raise the topic of weight and health early and regularly; (iii) use strengths‐based language emphasizing health over weight; (iv) use collaborative goal‐setting to engage children and parents and (v) augment discussions with appropriate tools and resources. Guidance on how to implement these principles and how to negotiate relevant contextual factors (e.g. age, culture and disability) is still needed. Conclusion: Despite agreement on a number of guiding principles, evidence‐based weight‐related communication best practices are lacking. Rigorous, empirical evaluations of communication approaches are urgently required, especially those that include children's perspectives.